Analisis Kualitas Jasa Menggunakan Metode Servqual (Studi Pada Joss Laundry Jatinangor) - Nadira Adinda Putri Asmara; Tetty Herawaty; Dian Fordian (Liquidity, 2025)
Service quality encourages the formation of strong bonds between customers and companies. Customer satisfaction is achieved when their expectations and needs are consistently met through the services provided. This research was conducted at Joss Laundry Jatinangor. To understand and meet customer expectations, the SERVQUAL method was used to measure the gap between customer expectations and perceptions across five dimensions of service quality. The study was also supported by validity and reliability tests to ensure the accuracy of the data. Out of 20 attributes analyzed, 9 were found to have negative gap values, indicating that customer perceptions were still below their expectations. The largest negative gap was identified in the attribute of timeliness in service completion, with a gap value of -0.35. Based on these findings, it is recommended that Joss Laundry Jatinangor prioritize improvements in service timeliness and conduct regular evaluations of other negatively scored attributes. Enhancing operational efficiency and providing employee training are essential steps to improve overall service quality and maintain customer satisfaction.